Attacks on Shen et. al.’s remote user authentication scheme and defense* - Pathan, Al-Sakib Khan; Hong, Choong Seon (2006)
The intent of this paper is to propose an efficient timestamp-based password authentication scheme using smart cards. We show various types of forgery attacks against Shen et. al.’s timestamp-based scheme and improve their scheme to ensure robust security for the remote authentication process keeping almost all the advantages that were present in their scheme. Our scheme successfully defends the attacks that could be launched against other related previous schemes.